A systematic review and meta‐analysis of the mental health symptoms during the Covid‐19 pandemic in Southeast Asia. Issue 2 (26th November 2021) - Pappa, Sofia; Chen, Jiyao; Barnett, Joshua; Chang, Anabel; Dong, Rebecca Kechen; Xu, Wen; Yin, Allen; Chen, Bryan Z.; Delios, Andrew Yilong; Chen, Richard Z.; Miller, Saylor; Wan, Xue; et al.
Abstract : Aims: The Covid‐19 pandemic has had a substantial impact on the mental health of the general public and high‐risk groups worldwide. Due to its proximity and close links to China, Southeast Asia was one of the first regions to be affected by the outbreak. The aim of this systematic review was to evaluate the prevalence of anxiety, depression and insomnia in the general adult population and healthcare workers (HCWs) in Southeast Asia during the course of the first year of the pandemic. Methods: Several literature databases were systemically searched for articles published up to February 2021 and two reviewers independently evaluated all relevant studies using pre‐determined criteria. The prevalence rates of mental health symptoms were calculated using a random‐effect meta‐analysis model. Results: In total, 32 samples from 25 studies with 20 352 participants were included. Anxiety was assessed in all 25 studies and depression in 15 studies with pooled prevalence rates of 22% and 16%, respectively. Only two studies assessed insomnia, which was estimated at 19%. The prevalence of anxiety and depression was similar among frontline HCWs (18%), general HCWs (17%), and students (20%) while being noticeably higher in the general population (27%). Conclusions: This is the first systematic review to investigate the mental health impact of the Covid‐19 pandemic in Southeast Asia. A considerable proportion of the general population and HCWs reported mild to moderate symptoms of anxiety and depression; the pooled prevalence rater, however, remain significantly lower than those reported in other areas such as China and Europe.